Brief Report: Anti–Calponin 3 Autoantibodies: A Newly Identified Specificity in Patients With Sjögren's Syndrome. Issue 10 (3rd September 2018) - Birnbaum, Julius; Hoke, Ahmet; Lalji, Aliya; Calabresi, Peter; Bhargava, Pavan; Casciola‐Rosen, Livia
Abstract : Objective: Autoantibodies are clinically useful for phenotyping patients across the spectrum of autoimmune rheumatic diseases. Using serum from a patient with Sjögren's syndrome (SS), we detected a new specificity by immunoblotting. This study was undertaken to identify this autoantibody and to evaluate its disease specificity. Methods: A prominent 40‐kd band was detected when immunoblotting was performed using SS patient serum and lysate from rat dorsal root ganglia (DRGs). Using 2‐dimensional gel electrophoresis and liquid chromatography tandem mass spectrometry peptide sequencing, the autoantigen was identified as calponin 3. Anti–calponin 3 antibodies were evaluated in sera from patients with primary SS (n = 209), patients with systemic lupus erythematosus (SLE; n = 138), patients with myositis (n = 138), patients with multiple sclerosis (MS; n = 44), and healthy controls (n = 46) by enzyme‐linked immunosorbent assay. Expression of calponin 3 was assessed by immunohistochemistry. Results: Calponin 3 was identified as a new autoantigen. Anti–calponin 3 antibodies were detected in 23 (11.0%) of the 209 SS patients, 12 (8.7%) of the 138 SLE patients, 7 (5.1%) of the 138 myositis patients, 3 (6.8%) of the 44 MS patients, and 1 (2.2%) of the 46 healthy controls. Among SS patients, the frequency of anti–calponin 3 antibodies was highest in those with neuropathies (7 [17.9%] of 39). In this subset, the frequency of anti–calponin 3 antibodies differed significantly from that in the control group ( P = 0.02). Calponin 3 was expressed primarily in rat DRG perineuronal satellite cells but not neurons. Conclusion: Calponin 3 is a novel autoantigen. Antibodies against this protein are found in SS and associate with the subset of patients experiencing neuropathies. Intriguingly, we found that calponin 3 is expressed in DRG perineuronal satellite cells, suggesting that these may be a target in SS.